Integration of pharmacodynamics, network pharmacology and metabolomics to elucidate the effect and mechanism of Jingfang Granule in the treatment of Paraquat induced Pulmonary fibrosis - Rujing Yue; Tianye Yang; Dejun Niu; Zhen Zeng; Xishuang Wang; Lihong Pan; Jingchun Yao (PLoS ONE, 2025)
Objective One of the main risk factors of COVID-19 is Pulmonary fibrosis (PF). The protective effect of Jingfang Granule (JF) to bleomycin-induced PF has been confirmed in our previous studies. This work was designed to reveal the effect and mechanism of JF on PF which induced by Paraquat (PQ). Methods In this study, the PF mice model was induced by PQ with the administration of 1, 0.5, and 0.25 g/kg JF or Nintedanib (NTNB) 45 mg/kg by oral administration. The ameliorating effects of JF were reflected by the survival curve and lung coefficient. And the pathological alterations of lung were observed by H&E, Masson and Sirius red staining. Then, the expression of fibrosis-associated protein α-SMA and TGFβ1/Smad2,3 signaling pathway was detected by immunohistochemistry and western blot. An integrated approach combined metabolomics with network pharmacology was applied to recognize the mechanism of JF on ameliorated the PQ-induced PF, and the result of integrated was verified by western blot. Results The experiment results showed that JF could inhibit the progression of PQ-induced PF and delay the death of mice after PQ poisoning, and the inhibit effect was similar to NTNB. JF also reduced fibroblasts in lung tissue of the PF mice model by significantly down- regulated the expression of α-SMA and TGFβ1/Smad2,3 signaling pathway. In addition, JF intervened 16 serum metabolites compared with PQ-induced PF mice, and the differential metabolites were linked 241 corresponding targeted proteins obtained by database, which have 79 common targets to JF related targets. The integrated results of metabolomics, network pharmacology and western blot showed that apoptosis was a crucial way for JF to relieve the PQ-induced PF, and JF regulated the signals of Bcl-2, Bax, Caspase-3 protein and PI3k/Akt pathway to inhibit the apoptosis. Conclusion These findings demonstrate that JF down-regulated the TGFβ1/Smad2,3 signaling pathway to reduce the fibroblasts, regulate the expression of Bcl-2, Bax, Caspase-3 and PI3k/Akt pathway to inhibit the apoptosis, and display a favorable effect on inhibiting the development of pulmonary fibrosis and delaying the death of PQ-induced PF mice.